BUILDING MONITORING SYSTEM BASED ON ZIGBEE - Firdaus Kurniawan; Hira Meidia (Jurnal Ilmu Komputer dan Informasi, 2013)
This paper presents the building monitoring system that can determine the building condition in real time and ensure the safety of building operations. This monitoring building system can detect the ambient, CO gas, fan, water leak, and also intrusion detectors, through a wired sensor network. Then the data is processed by a main controller to generate a report that sent to the inspectors through ZigBee and / or sound an alarm if the situation is considered dangerous. Prototype of this monitoring system shows precision and stability with minimal error rate. Main controller can receive data from the sensor network properly and send it through ZigBee modules.